A high mechanical strength aerogel thermal insulation material and preparation method thereof
The method enhances the mechanical properties of aerogel composites by fiber modification and binder introduction, addressing the limitations of existing aerogels in strength and toughness, resulting in high-temperature resistant materials with low thermal conductivity.
Patent Information
- Application Number
- CN202411568815.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Existing aerogel composites used in thermal insulation materials face challenges in achieving high mechanical strength and toughness while maintaining low density and low thermal conductivity, particularly for large-sized components, which limits their application in fields like aerospace and nuclear power.
A method involving fiber modification, sol preparation and impregnation, aging and gel modification, supercritical drying, and high-temperature sintering is employed to enhance the mechanical properties of oxide aerogel thermal insulation materials by introducing a binder precursor solution to improve bonding between fibers and aerogel particles, forming chemical and physical bonds at the nanoscale.
The method results in aerogel composites with high mechanical strength, temperature resistance, and low thermal conductivity, suitable for high-temperature applications, with improved compressive and bending strengths without significantly affecting thermal insulation performance.
Smart Images

Figure CN119059832B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel thermal insulation materials, and particularly relates to a high mechanical strength aerogel thermal insulation material and a preparation method thereof. Background Art
[0002] Aerogel is a low-density nanoporous material with extremely low thermal conductivity (for example, the room temperature thermal conductivity of silica aerogel is as low as 0.012W / (m·K)), and is a new type of thermal insulation material. Common oxide (silicon oxide, aluminum oxide, zirconium oxide, etc.) aerogels have high temperature resistance and can exert their excellent thermal insulation function at 400-1500℃, and have broad application prospects in aerospace, shipbuilding, nuclear power and other fields.
[0003] Due to its intrinsic brittleness and high porosity, the mechanical properties of oxide aerogels are usually 3-5 orders of magnitude lower than those of dense materials of the same components. They are easily damaged during preparation and use, and are difficult to be directly used as thermal insulation materials. The mechanical properties of aerogels are improved to a certain extent by preparing aerogel composites through fiber reinforcement. For example: the compressive strength (10% strain) and flexural strength of mullite fiber reinforced silica aerogel composites are 0.98MPa and 1.31MPa respectively; the compressive strength (3% strain) and flexural strength of mullite fiber reinforced alumina aerogel composites are 0.13MPa and 0.91MPa respectively. Fiber reinforcement gives oxide aerogel composites better block properties, which can be formed into larger parts.
[0004] However, the rapid development of aerospace, nuclear power, industrial furnaces and other fields has put forward more stringent requirements on the comprehensive performance of high-temperature thermal insulation materials. Oxide aerogel composites have good thermal insulation properties, but the corresponding mechanical properties are difficult to meet new requirements. When preparing and applying large-size thin-walled parts, the mechanical strength of aerogel composites is particularly insufficient, which has become an important technical bottleneck restricting its further application and development. Improving the mechanical properties by increasing the density of aerogel composites often has limited effect and greatly sacrifices the lightness and thermal insulation properties of the material.
[0005] Therefore, it remains a major challenge to improve the mechanical strength and toughness of aerogel insulation materials while maintaining their low density and low thermal conductivity properties in order to prepare large-sized special-shaped components of lightweight and high-strength aerogel insulation composite materials. Summary of the invention
[0006] In view of the problem that the mechanical properties are often improved by increasing the density of aerogel composite materials in the prior art, which often has limited effect and greatly sacrifices the lightness and thermal insulation performance of the material, the present invention provides a high mechanical strength aerogel thermal insulation material and a preparation method thereof, and prepares a high mechanical strength high temperature resistant oxide aerogel thermal insulation material. The high mechanical strength aerogel thermal insulation material prepared by the present invention has the characteristics of high temperature resistance, low density, high specific strength, and low thermal conductivity, and can be used as a high temperature thermal insulation material in the fields of aerospace, nuclear power, etc.
[0007] The technical solution of the present invention is as follows:
[0008] The preparation method of the invention comprises five steps: fiber modification, sol preparation and impregnation, aging and gel modification, supercritical drying and high-temperature sintering.
[0009] The present invention prepares an oxide aerogel thermal insulation material with high mechanical strength through fiber modification, sol preparation and impregnation, aging and gel modification, supercritical drying, and high-temperature sintering. The fiber reinforcement phase is modified by a binder solution, the wet gel is liquid-phase modified by a binder solution, and the aerogel matrix and its composite material are strengthened through physical and chemical reactions, thereby significantly improving the mechanical properties of the aerogel thermal insulation material.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] A method for preparing a high mechanical strength aerogel thermal insulation material comprises the following steps:
[0012] 1) Fiber modification:
[0013] The long fiber is immersed in a binder precursor solution with water as solvent, maintained at 40-90° C. for 2-12 hours, and then taken out and dried to constant weight to obtain a modified fiber;
[0014] The long fiber is selected from one of mullite fiber, quartz fiber, alumina fiber and zirconia fiber, with an average diameter of 0.5-5 μm and a length of 100-500 mm;
[0015] The binder precursor in the binder precursor solution is selected from boric acid or phosphoric acid, and the mass fraction of the binder precursor is 4-10% of the binder precursor solution;
[0016] 2) Sol preparation and impregnation:
[0017] Under a pressure of -0.1 to 0 MPa, the oxide sol is impregnated into the pores of the modified fiber obtained in the above step for 0.5 to 3 hours to obtain a sol-fiber mixture;
[0018] The oxide sol is selected from silicon oxide, aluminum oxide, and zirconium oxide sol;
[0019] 3) Aging and gel modification:
[0020] The sol-fiber mixture obtained in the above step is kept at 40-75° C. for 6-24 hours to form a gel-fiber composite, and then the gel-fiber composite is immersed in a binder precursor solution with alcohol as a solvent and kept at 40-95° C. for 12-48 hours to obtain a modified gel-fiber composite;
[0021] The binder precursor in the binder precursor solution is selected from boric acid or phosphoric acid;
[0022] The alcohol is selected from ethanol, methanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol;
[0023] The binder precursor solution using alcohol as solvent has a mass fraction of 5-15%;
[0024] 4) Supercritical drying:
[0025] The modified gel-fiber composite obtained in the above step is placed in an autoclave, and after adding alcohol, it is kept sealed, heated to above the critical point of the alcohol and kept for 2-10 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, to obtain an aerogel composite material;
[0026] The alcohol is one of ethanol, methanol, isopropanol, n-propanol, n-butanol, sec-butanol and tert-butanol; the volume ratio of the alcohol to the gel-fiber complex is (1-3):1;
[0027] 5) High temperature sintering:
[0028] The aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 600-1100°C at a heating rate of 1-5°C / min, and maintained for 1-10h, and naturally cooled to obtain a high mechanical strength aerogel thermal insulation material. The typical properties of the high mechanical strength aerogel thermal insulation material are as follows:
[0029] ① Mullite fiber reinforced silica aerogel thermal insulation composite material, heat resistant temperature reaches 900℃, density is 0.35-0.39 g / cm 3 The thermal conductivity at room temperature and 800℃ are 0.022-0.026 W / (m·K) and 0.038-0.049 W / (m·K) respectively, the compressive strength (3% deformation) is 0.53-0.97 MPa, and the bending strength is 3.2-4.5 MPa;
[0030] ② Mullite fiber reinforced alumina aerogel thermal insulation composite material, with a heat resistance temperature of 1200°C and a density of 0.30-0.32 g / cm 3The thermal conductivity at room temperature and 1100℃ are 0.028-0.030 W / (m·K) and 0.060-0.067W / (m·K), respectively. The compressive strength (3% deformation) is 0.53-0.68 MPa, and the bending strength is 2.5-3.1 MPa.
[0031] ③ Zirconia fiber reinforced zirconia aerogel thermal insulation composite material, with a heat resistance temperature of 1100°C and a density of 0.33-0.34 g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.021-0.024 W / (m·K) and 0.033-0.038 W / (m·K) respectively, the compressive strength (3% deformation) is 0.53-0.64 MPa, and the flexural strength is 2.7-2.9 MPa.
[0032] In the present invention:
[0033] The alcohol described in step 3) and step 4) is preferably ethanol or methanol.
[0034] The present invention also relates to a high mechanical strength aerogel thermal insulation material, which is obtained by the above-mentioned method for preparing a high mechanical strength aerogel thermal insulation material. The typical properties of the high mechanical strength aerogel thermal insulation material are as follows:
[0035] ① Mullite fiber reinforced silica aerogel thermal insulation composite material, heat resistant temperature reaches 900℃, density is 0.35-0.39 g / cm 3 The thermal conductivity at room temperature and 800℃ are 0.022-0.026 W / (m·K) and 0.038-0.049 W / (m·K) respectively, the compressive strength (3% deformation) is 0.53-0.97 MPa, and the bending strength is 3.2-4.5 MPa;
[0036] ② Mullite fiber reinforced alumina aerogel thermal insulation composite material, with a heat resistance temperature of 1200°C and a density of 0.30-0.32 g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.028-0.030 W / (m·K) and 0.060-0.067W / (m·K), respectively. The compressive strength (3% deformation) is 0.53-0.68 MPa, and the bending strength is 2.5-3.1 MPa.
[0037] ③ Zirconia fiber reinforced zirconia aerogel thermal insulation composite material, with a heat resistance temperature of 1100°C and a density of 0.33-0.34 g / cm 3The thermal conductivity at room temperature and 1100℃ are 0.021-0.024 W / (m·K) and 0.033-0.038 W / (m·K) respectively, the compressive strength (3% deformation) is 0.53-0.64 MPa, and the flexural strength is 2.7-2.9 MPa.
[0038] Compared with the prior art, the present invention has the following advantages:
[0039] 1. The method for preparing a high mechanical strength aerogel thermal insulation material described in the present invention is to modify the wet gel in liquid phase, immerse the wet gel in an inorganic acid (precursor of the binder, boric acid, phosphoric acid, etc.) solution, and react the hydroxyl groups on the surface of the gel particles with the inorganic acid, so that the binder is uniformly introduced into the network structure of the gel at a nanometer scale, and further condensation reaction is performed during the high-temperature sintering process to bond the aerogel particles together, and the force between the particles is enhanced, which greatly improves the skeleton strength of the aerogel, not only significantly improves the mechanical properties, but also improves the ability to resist sintering, and improves the temperature resistance of the aerogel. By adjusting the concentration of the inorganic acid solution, the content of the binder is relatively low, and at the same time, the bulk thermal conductivity of the binder is low, and it is dispersed between the particles at a nanometer scale, which ultimately has no significant effect on the solid-state thermal conduction and pore structure of the aerogel skeleton, and can still maintain a very low thermal conductivity.
[0040] 2. A method for preparing a high mechanical strength aerogel thermal insulation material according to the present invention, by introducing a binder into a long fiber reinforcement phase, the binder forms a chemical bond with the fiber surface, and significantly improves the interfacial bonding force after the aerogel matrix and the fiber are composited. The fiber reinforcement phase is immersed in an inorganic acid (precursor of the binder, boric acid, phosphoric acid, etc.) solution, so that the binder precursor is uniformly introduced into the fiber and combined with the fiber surface. The inorganic acid has a certain etching effect on the fiber surface, which can increase the surface roughness and increase the contact area between the aerogel and the fiber. After the aerogel and the fiber are composited, the binder bridges the fiber and the aerogel through high-temperature sintering, forming a chemical coupling and physical anchoring effect, which significantly improves the interfacial bonding force between the aerogel and the fiber. This method increases the force and deformation resistance between the aerogel and the fiber, and significantly improves the pressure-bearing performance of the aerogel composite material. At the same time, the aerogel composite material will produce a more significant fiber pull-out-energy consumption effect when it is pulled, and the material toughness will be greatly improved.
[0041] 3. The method for preparing a high mechanical strength aerogel thermal insulation material described in the present invention uses a binder precursor solution to perform liquid phase modification on wet gel and fiber respectively, which can evenly introduce nanoscale binder components into the aerogel and fiber to optimize the bonding enhancement effect. At the same time, the solid-state thermal conduction of the aerogel itself and the solid-state thermal conduction between the aerogel and the fiber are not significantly increased. The mechanical strength of the prepared aerogel composite material is significantly improved while the thermal conductivity is not significantly affected. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a scanning electron microscope photograph of the alumina aerogel in the thermal insulation material prepared in Example 2 of the present invention after heat treatment at 1200° C. for 2 hours;
[0043] Figure 2 This is a scanning electron microscope photograph of the thermal insulation material (alumina aerogel composite material) prepared in Example 2 of the present invention after heat treatment at 1200° C. for 2 hours. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.
[0045] Embodiment 1:
[0046] A method for preparing a high mechanical strength aerogel thermal insulation material comprises the following steps:
[0047] 1) Fiber modification:
[0048] The mullite long fiber is immersed in a boric acid solution with water as solvent, maintained at 60°C for 8 hours, taken out and dried to constant weight to obtain the modified mullite fiber;
[0049] The average diameter of mullite long fiber is 4μm and the length is 380mm;
[0050] The mass fraction of the boric acid solution is 6.5%;
[0051] 2) Sol preparation and impregnation:
[0052] Under a pressure of -0.1 MPa, the silica sol is impregnated into the pores of the modified mullite fiber obtained in the above step for 1.5 hours to obtain a sol-fiber mixture;
[0053] 3) Aging and gel modification:
[0054] The sol-fiber obtained in the above step is kept at 50° C. for 18 hours to form a gel-fiber complex, and then the gel-fiber complex is immersed in a boric acid solution with ethanol as a solvent and kept at 60° C. for 24 hours to obtain a modified gel-fiber complex;
[0055] The mass fraction of the boric acid solution is 6.5%;
[0056] 4) Supercritical drying:
[0057] The modified gel-fiber composite obtained in the above step is placed in an autoclave, and after adding ethanol, it is kept sealed, heated to above the critical point of ethanol and kept for 4 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, to obtain an aerogel composite material;
[0058] The volume ratio of ethanol to gel-fiber complex was 1:1;
[0059] 5) High temperature sintering:
[0060] The aerogel composite material blank obtained in the above step was placed in a high-temperature furnace, heated from room temperature to 700°C at a heating rate of 3°C / min, and maintained for 4 hours, and naturally cooled to obtain a mullite fiber composite silica aerogel insulation material with the following properties:
[0061] Heat-resistant temperature reaches 900℃, density is 0.35 g / cm 3 The thermal conductivity at room temperature and 800℃ are 0.023 W / (m·K) and 0.045 W / (m·K) respectively, the compressive strength (3% deformation) is 0.71 MPa, and the bending strength is 3.6 MPa.
[0062] Embodiment 2:
[0063] A method for preparing a high mechanical strength aerogel thermal insulation material comprises the following steps:
[0064] 1) Fiber modification:
[0065] The mullite long fiber is immersed in a phosphoric acid solution with water as solvent, maintained at 65° C. for 8 hours, taken out and dried to constant weight to obtain the modified mullite fiber;
[0066] The average diameter of mullite long fibers is 4.5 μm and the length is 300 mm;
[0067] The mass fraction of phosphoric acid solution is 7.5%;
[0068] 2) Sol preparation and impregnation:
[0069] Under a pressure of -0.1 MPa, the alumina sol is impregnated into the pores of the modified mullite fiber obtained in the above step for 1 hour to obtain a sol-fiber mixture;
[0070] 3) Aging and gel modification:
[0071] The sol-fiber mixture obtained in the above step is kept at 60° C. for 12 hours to form a gel-fiber complex, and then the gel-fiber complex is immersed in a phosphoric acid solution with isopropanol as a solvent and kept at 65° C. for 24 hours to obtain a modified gel-fiber complex;
[0072] The mass fraction of phosphoric acid solution is 9%;
[0073] 4) Supercritical drying:
[0074] The modified gel-fiber composite obtained in the above step is placed in an autoclave, isopropanol is added and kept sealed, heated to above the critical point of isopropanol and kept for 6 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining an aerogel composite material;
[0075] The volume ratio of isopropyl alcohol to gel-fiber complex was 1:1;
[0076] 5) High temperature sintering:
[0077] The aerogel composite material blank obtained in the above step was placed in a high-temperature furnace, heated from room temperature to 1000°C at a heating rate of 2°C / min, and maintained for 4 hours, and naturally cooled to obtain a mullite fiber composite alumina aerogel insulation material with the following properties: heat resistance temperature reached 1200°C, density was 0.32 g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.030 W / (m·K) and 0.067W / (m·K) respectively, the compressive strength (3% deformation) is 0.68 MPa, and the bending strength is 3.1 MPa.
[0078] Embodiment 3:
[0079] A method for preparing a high mechanical strength aerogel thermal insulation material comprises the following steps:
[0080] 1) Fiber modification:
[0081] The zirconia long fiber is immersed in a phosphoric acid solution with water as solvent, maintained at 50° C. for 9 hours, taken out and dried to constant weight to obtain a modified zirconia fiber;
[0082] The average diameter of the zirconia fiber is 2 μm and the length is 200 mm;
[0083] The mass fraction of phosphoric acid solution is 6%;
[0084] 2) Sol preparation and impregnation:
[0085] Under a pressure of -0.1 MPa, the zirconium oxide sol is impregnated into the pores of the modified zirconium oxide fiber obtained in the above step for 2.5 hours to obtain a sol-fiber mixture;
[0086] 3) Aging and gel modification:
[0087] The sol-fiber mixture obtained in the above step is kept at 55° C. for 8 hours to form a gel-fiber complex, and then the gel-fiber complex is immersed in a phosphoric acid solution with n-butanol as a solvent and kept at 65° C. for 36 hours to obtain a modified gel-fiber complex;
[0088] The mass fraction of phosphoric acid solution is 10%;
[0089] 4) Supercritical drying:
[0090] The modified gel-fiber composite obtained in the above step is placed in an autoclave, and after adding n-butanol, it is kept sealed, heated to above the critical point of alcohol and kept for 5 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, to obtain an aerogel composite material;
[0091] The volume ratio of n-butanol to gel-fiber complex was 1.5:1;
[0092] 5) High temperature sintering:
[0093] The aerogel composite material blank obtained in the above step was placed in a high-temperature furnace, heated from room temperature to 950°C at a heating rate of 2.5°C / min, and maintained for 6 hours, and naturally cooled to obtain a zirconia fiber composite zirconia aerogel insulation material with the following properties: heat resistance temperature reached 1100°C, density was 0.33g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.024 W / (m·K) and 0.038 W / (m·K) respectively, the compressive strength (3% deformation) is 0.53 MPa, and the bending strength is 2.7 MPa.
[0094] Embodiment 4:
[0095] A method for preparing a high mechanical strength aerogel thermal insulation material comprises the following steps:
[0096] 1) Fiber modification:
[0097] The mullite long fiber is immersed in a boric acid solution with water as solvent, maintained at 90°C for 2 hours, taken out and dried to constant weight to obtain the modified mullite fiber;
[0098] The average diameter of mullite long fiber is 5μm and the length is 500mm;
[0099] The mass fraction of the boric acid solution is 10%;
[0100] 2) Sol preparation and impregnation:
[0101] Under a pressure of 0 MPa, the silica sol is impregnated into the pores of the modified mullite fiber obtained in the above step for 3 hours to obtain a sol-fiber mixture;
[0102] 3) Aging and gel modification:
[0103] The sol-fiber obtained in the above step is kept at 75° C. for 6 hours to form a gel-fiber complex, and then the gel-fiber complex is immersed in a boric acid solution with ethanol as a solvent and kept at 95° C. for 12 hours to obtain a modified gel-fiber complex;
[0104] The mass fraction of the boric acid solution is 15%;
[0105] 4) Supercritical drying:
[0106] The modified gel-fiber composite obtained in the above step is placed in an autoclave, and after adding ethanol, it is kept sealed, heated to above the critical point of ethanol and kept for 10 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining an aerogel composite material;
[0107] The volume ratio of ethanol to gel-fiber complex was 3:1;
[0108] 5) High temperature sintering:
[0109] The aerogel composite material blank obtained in the above step was placed in a high-temperature furnace, heated from room temperature to 700°C at a heating rate of 5°C / min, and maintained for 10 hours, and naturally cooled to obtain a mullite fiber composite silica aerogel insulation material with the following properties: heat resistance temperature reached 900°C, density was 0.39 g / cm 3 The thermal conductivity at room temperature and 800℃ are 0.026 W / (m·K) and 0.049 W / (m·K) respectively, the compressive strength (3% deformation) is 0.97 MPa, and the bending strength is 4.5 MPa.
[0110] Embodiment 5:
[0111] A method for preparing a high mechanical strength aerogel thermal insulation material comprises the following steps:
[0112] 1) Fiber modification:
[0113] The mullite long fiber is immersed in a phosphoric acid solution with water as solvent, maintained at 40° C. for 12 hours, taken out and dried to constant weight to obtain the modified mullite fiber;
[0114] The average diameter of mullite long fibers is 4.5 μm and the length is 300 mm;
[0115] The mass fraction of phosphoric acid solution is 4%;
[0116] 2) Sol preparation and impregnation:
[0117] Under a pressure of -0.1 MPa, the alumina sol is impregnated into the pores of the modified mullite fiber obtained in the above step for 1 hour to obtain a sol-fiber mixture;
[0118] 3) Aging and gel modification:
[0119] The sol-fiber mixture obtained in the above step is kept at 40° C. for 24 hours to form a gel-fiber complex, and then the gel-fiber complex is immersed in a phosphoric acid solution with isopropanol as a solvent and kept at 40° C. for 48 hours to obtain a modified gel-fiber complex;
[0120] The mass fraction of phosphoric acid solution is 5%;
[0121] 4) Supercritical drying:
[0122] The modified gel-fiber composite obtained in the above step is placed in an autoclave, isopropanol is added and kept sealed, heated to above the critical point of isopropanol and kept for 4 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining an aerogel composite material;
[0123] The volume ratio of isopropyl alcohol to gel-fiber complex was 1:1;
[0124] 5) High temperature sintering:
[0125] The aerogel composite material blank obtained in the above step was placed in a high-temperature furnace, heated from room temperature to 1000°C at a heating rate of 5°C / min, and maintained for 2 hours, and naturally cooled to obtain a mullite fiber composite alumina aerogel insulation material with the following properties:
[0126] Heat-resistant temperature reaches 1200℃, density is 0.30 g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.028 W / (m·K) and 0.060W / (m·K) respectively, the compressive strength (3% deformation) is 0.53 MPa, and the bending strength is 2.5 MPa.
[0127] Embodiment 6:
[0128] A method for preparing a high mechanical strength aerogel thermal insulation material comprises the following steps:
[0129] 1) Fiber modification:
[0130] The zirconia long fiber is immersed in a phosphoric acid solution with water as solvent, maintained at 50° C. for 9 hours, taken out and dried to constant weight to obtain a modified zirconia fiber;
[0131] The average diameter of the zirconia fiber is 0.5 μm and the length is 100 mm;
[0132] The mass fraction of phosphoric acid solution is 6%;
[0133] 2) Sol preparation and impregnation:
[0134] Under a pressure of -0.1 MPa, the zirconium oxide sol is impregnated into the pores of the modified zirconium oxide fiber obtained in the above step for 2.5 hours to obtain a sol-fiber mixture;
[0135] 3) Aging and gel modification:
[0136] The sol-fiber mixture obtained in the above step is kept at 60° C. for 8 hours to form a gel-fiber complex, and then the gel-fiber complex is immersed in a phosphoric acid solution with n-propanol as a solvent and kept at 65° C. for 28 hours to obtain a modified gel-fiber complex;
[0137] The mass fraction of phosphoric acid solution is 10%;
[0138] 4) Supercritical drying:
[0139] The modified gel-fiber composite obtained in the above step is placed in an autoclave, and after adding n-propanol, it is kept airtight, heated to above the critical point of n-propanol and kept for 5 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, to obtain an aerogel composite material;
[0140] The volume ratio of n-propanol to gel-fiber complex was 1.2:1;
[0141] 5) High temperature sintering:
[0142] The aerogel composite material blank obtained in the above step was placed in a high-temperature furnace, heated from room temperature to 950°C at a heating rate of 2°C / min, and maintained for 6 hours, and naturally cooled to obtain a zirconia fiber composite zirconia aerogel insulation material with the following properties:
[0143] Heat-resistant temperature reaches 1000℃, density is 0.34g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.021 W / (m·K) and 0.033 W / (m·K) respectively, the compressive strength (3% deformation) is 0.64 MPa, and the bending strength is 2.9 MPa.
[0144] Embodiment 7:
[0145] A method for preparing a high mechanical strength aerogel thermal insulation material comprises the following steps:
[0146] 1) Fiber modification:
[0147] The quartz long fiber was immersed in a boric acid solution with water as solvent, kept at 50°C for 8 hours, and then taken out and dried to constant weight to obtain the modified quartz fiber;
[0148] The average diameter of mullite long fiber is 1.5μm and the length is 320mm;
[0149] The mass fraction of the boric acid solution is 6.5%;
[0150] 2) Sol preparation and impregnation:
[0151] Under a pressure of -0.1 MPa, the silica sol is impregnated into the pores of the modified quartz fiber obtained in the above step for 1.5 hours to obtain a sol-fiber mixture;
[0152] 3) Aging and gel modification:
[0153] The sol-fiber obtained in the above step is kept at 50° C. for 20 hours to form a gel-fiber complex, and then the gel-fiber complex is immersed in a boric acid solution with ethanol as a solvent and kept at 60° C. for 18 hours to obtain a modified gel-fiber complex;
[0154] The mass fraction of the boric acid solution is 6.5%;
[0155] 4) Supercritical drying:
[0156] The modified gel-fiber composite obtained in the above step is placed in an autoclave, and after adding ethanol, it is kept sealed, heated to above the critical point of ethanol and kept for 4 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, to obtain an aerogel composite material;
[0157] The volume ratio of ethanol to gel-fiber complex was 1:1;
[0158] 5) High temperature sintering:
[0159] The aerogel composite material blank obtained in the above step was placed in a high-temperature furnace, heated from room temperature to 700°C at a heating rate of 4°C / min, and maintained for 4 hours, and naturally cooled to obtain a quartz fiber reinforced silica aerogel insulation material with the following properties:
[0160] Heat-resistant temperature reaches 900℃, density is 0.35 g / cm 3 The thermal conductivity at room temperature and 800℃ are 0.022 W / (m·K) and 0.038 W / (m·K) respectively, the compressive strength (3% deformation) is 0.53 MPa, and the bending strength is 4.0 MPa.
[0161] Embodiment 8:
[0162] A method for preparing a high mechanical strength aerogel thermal insulation material comprises the following steps:
[0163] 1) Fiber modification:
[0164] The alumina long fibers were immersed in a boric acid solution with water as solvent, kept at 60°C for 8 hours, and then taken out and dried to constant weight to obtain modified alumina fibers;
[0165] The average diameter of alumina long fibers is 4 μm and the length is 350 mm;
[0166] The mass fraction of the boric acid solution is 6.5%;
[0167] 2) Sol preparation and impregnation:
[0168] Under a pressure of -0.1 MPa, the silica sol was impregnated into the pores of the modified alumina fibers obtained in the above step for 1.5 h to obtain a sol-fiber mixture;
[0169] 3) Aging and gel modification:
[0170] The sol-fiber obtained in the above step is kept at 50° C. for 18 hours to form a gel-fiber complex, and then the gel-fiber complex is immersed in a boric acid solution with ethanol as a solvent and kept at 60° C. for 24 hours to obtain a modified gel-fiber complex;
[0171] The mass fraction of the boric acid solution is 6.5%;
[0172] 4) Supercritical drying:
[0173] The modified gel-fiber composite obtained in the above step is placed in an autoclave, and after adding ethanol, it is kept sealed, heated to above the critical point of ethanol and kept for 4 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, to obtain an aerogel composite material;
[0174] The volume ratio of ethanol to gel-fiber complex was 1:1;
[0175] 5) High temperature sintering:
[0176] The aerogel composite material blank obtained in the above step was placed in a high-temperature furnace, heated from room temperature to 700°C at a heating rate of 3°C / min, and maintained for 4 hours, and naturally cooled to obtain an alumina fiber reinforced silica aerogel insulation material with the following properties:
[0177] Heat-resistant temperature reaches 900℃, density is 0.35 g / cm 3 The thermal conductivity at room temperature and 800℃ are 0.025 W / (m·K) and 0.048 W / (m·K) respectively, the compressive strength (3% deformation) is 0.74 MPa, and the bending strength is 3.2 MPa.
[0178] It can be seen from the examples that hydroxyl groups (Si-OH, Al-OH, Zr-OH) are distributed on the surface of the skeleton particles of the silicon oxide, aluminum oxide, and zirconium oxide aerogels in step 2) of the preparation method of the present invention, and hydroxyl groups (Si-OH, Al-OH, Zr-OH) are also distributed on the surface of the mullite fiber, quartz fiber, aluminum oxide fiber, and zirconium oxide fiber in step 1). These hydroxyl groups can react with the binder in the binder precursor (boric acid, phosphoric acid) solution during the modification, aging, drying and sintering processes, that is, they react with the B-OH and P-OH of boric acid and phosphoric acid to form strong bridging oxygen bonds such as Si-OB, Al-OB, Si-OP, Al-OP, etc., thereby improving chemical bonding.
[0179] For example, the reaction formula of Si-OH of silica aerogel and boric acid is as follows:
[0180] -Si-OH + -B-OH = -Si-OB- + H2O
[0181] Therefore, the present invention uses a binder precursor (boric acid, phosphoric acid) solution to treat the fiber, which mainly produces two effects:
[0182] (1) Inorganic acids will ionize H in water + It has a certain etching effect on the fiber surface, which can increase its surface roughness and specific surface area. On the one hand, it increases the contact area between aerogel and fiber and strengthens the physical anchoring effect of aerogel on fiber. On the other hand, more hydroxyl groups (Si-OH, Al-OH, Zr-OH) will be produced on the fiber surface due to etching, and the number of reactions between the hydroxyl groups of aerogel and the hydroxyl groups on the fiber surface increases, thereby increasing the overall chemical bonding force between aerogel and fiber.
[0183] (2) The bonding between the binder and the fiber is mainly through the chemical bonding between the binder and the fiber surface. During the sintering process, the binder reacts with the hydroxyl groups on the surface of the aerogel particles and the fiber surface at the same time to form strong chemical bonds such as Al-OBO-Al, Al-OBO-Si, Al-OBO-Zr, Al-OPO-Al, Al-OPO-Si, and Al-OPO-Zr, thereby improving the bonding strength of the aerogel-fiber interface and the mechanical properties of the aerogel insulation material.
[0184] Hydroxyl groups (Si-OH, Al-OH, Zr-OH) are distributed on the surface of the skeleton particles of silica, alumina, and zirconia aerogel in step 2), and these hydroxyl groups can react with the binder during the modification, aging, drying, and sintering processes. Through the liquid phase modification process, the binder is uniformly introduced into the network structure of silica, alumina, and zirconia gels, and the hydroxyl groups (Si-OH, Al-OH, Zr-OH) on the surface of the skeleton particles react with B-OH and P-OH of boric acid and phosphoric acid to generate strong bridging oxygen bonds such as Si-OB, Al-OB, Si-OP, Al-OP, etc., which enhance the chemical bonding between aerogel particles, thereby improving the skeleton strength and macroscopic mechanical properties of the aerogel.
[0185] Comparative Example 1:
[0186] The difference between Comparative Example 1 and Example 1 is that the average diameter of the mullite long fiber is 10 μm, and the rest is the same as Example 1;
[0187] The thermal conductivity of the obtained aerogel insulation material at room temperature and 800°C is 0.026 W / (m·K) and 0.055 W / (m·K), respectively;
[0188] This indicates that the larger fiber diameter leads to increased heat conduction and thermal conductivity.
[0189] Comparative Example 2:
[0190] The difference between Comparative Example 2 and Example 1 is that the mass fraction of the boric acid solution in step 1) is 25%, and the rest is the same as Example 1;
[0191] The obtained aerogel insulation material has a density of 0.40 g / cm 3 The thermal conductivity at room temperature and 800℃ are 0.028 W / (m·K) and 0.061 W / (m·K) respectively, the compressive strength (3% deformation) is 1.1 MPa, and the bending strength is 4.8 MPa;
[0192] This indicates that the high mass fraction of the binder precursor solution leads to a significant increase in the density and mechanical properties of the thermal insulation material, while a significant increase in the thermal conductivity.
[0193] Comparative Example 3:
[0194] The difference between Comparative Example 3 and Example 1 is that the sintering temperature in step 5) is 500° C., and the rest is the same as Example 1;
[0195] The obtained aerogel insulation material has a compressive strength (3% deformation) of 0.34 MPa and a flexural strength of 2.0 MPa;
[0196] This indicates that the sintering temperature is too low, the sintering reaction of the binder is insufficient, and the strength of the thermal insulation material is significantly reduced.
[0197] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. Various process schemes that are not substantially different from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing a high mechanical strength aerogel thermal insulation material, characterized in that: The following steps are involved: 1) Fiber modification: The long fiber is immersed in a binder precursor solution with water as solvent, maintained at 40-90° C. for 2-12 hours, and then taken out and dried to constant weight to obtain a modified fiber; The long fiber is selected from one of mullite fiber, quartz fiber, alumina fiber and zirconia fiber, with an average diameter of 0.5-5 μm and a length of 100-500 mm; The binder precursor in the binder precursor solution is selected from boric acid or phosphoric acid, and the mass fraction of the binder precursor is 4-10% of the binder precursor solution; 2) Sol preparation and impregnation: Under a pressure of -0.1 to 0 MPa, the oxide sol is impregnated into the pores of the modified fiber obtained in the above step for 0.5 to 3 hours to obtain a sol-fiber mixture; The oxide sol is selected from silicon oxide, aluminum oxide, and zirconium oxide sol; 3) Aging and gel modification: The sol-fiber mixture obtained in the above step is kept at 40-75° C. for 6-24 hours to form a gel-fiber composite, and then the gel-fiber composite is immersed in a binder precursor solution with alcohol as a solvent and kept at 40-95° C. for 12-48 hours to obtain a modified gel-fiber composite; The binder precursor in the binder precursor solution is selected from boric acid or phosphoric acid; The alcohol is selected from ethanol, methanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol; The binder precursor solution using alcohol as solvent has a mass fraction of 5-15%; 4) Supercritical drying: The modified gel-fiber composite obtained in the above step is placed in an autoclave, and after adding alcohol, it is kept sealed, heated to above the critical point of the alcohol and kept for 2-10 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, to obtain an aerogel composite material; The alcohol is one of ethanol, methanol, isopropanol, n-propanol, n-butanol, sec-butanol and tert-butanol; the volume ratio of the alcohol to the gel-fiber complex is (1-3):1; 5) High temperature sintering: The aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 600-1100°C at a heating rate of 1-5°C / min, and maintained for 1-10h, and naturally cooled to obtain a high mechanical strength aerogel thermal insulation material. The typical properties of the high mechanical strength aerogel thermal insulation material are as follows: ① Mullite fiber reinforced silica aerogel thermal insulation composite material, heat resistant temperature reaches 900℃, density is 0.35-0.39 g / cm 3 The thermal conductivity at room temperature and 800℃ are 0.022-0.026 W / (m·K) and 0.038-0.049 W / (m·K) respectively, the compressive strength is 0.53-0.97 MPa at 3% deformation, and the bending strength is 3.2-4.5 MPa; ② Mullite fiber reinforced alumina aerogel thermal insulation composite material, with a heat resistance temperature of 1200°C and a density of 0.30-0.32 g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.028-0.030 W / (m·K) and 0.060-0.067W / (m·K) respectively, the compressive strength is 0.53-0.68 MPa at 3% deformation, and the bending strength is 2.5-3.1 MPa; ③ Zirconia fiber reinforced zirconia aerogel thermal insulation composite material, with a heat resistance temperature of 1100°C and a density of 0.33-0.34 g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.021-0.024 W / (m·K) and 0.033-0.038 W / (m·K) respectively, the compressive strength is 3% deformation is 0.53-0.64 MPa, and the bending strength is 2.7-2.9 MPa.
2. The method for preparing a high mechanical strength aerogel thermal insulation material according to claim 1, characterized in that: The alcohol described in step 3) and step 4) is ethanol or methanol.
3. A high mechanical strength aerogel thermal insulation material, characterized in that: The high mechanical strength aerogel thermal insulation material is obtained by the preparation method of claim 1 or 2, and the typical properties of the high mechanical strength aerogel thermal insulation material are as follows: ① Mullite fiber reinforced silica aerogel thermal insulation composite material, heat resistant temperature reaches 900℃, density is 0.35-0.39 g / cm 3 The thermal conductivity at room temperature and 800℃ are 0.022-0.026 W / (m·K) and 0.038-0.049 W / (m·K) respectively, the compressive strength is 0.53-0.97 MPa at 3% deformation, and the bending strength is 3.2-4.5 MPa; ② Mullite fiber reinforced alumina aerogel thermal insulation composite material, with a heat resistance temperature of 1200°C and a density of 0.30-0.32 g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.028-0.030 W / (m·K) and 0.060-0.067W / (m·K) respectively, the compressive strength is 0.53-0.68 MPa at 3% deformation, and the bending strength is 2.5-3.1 MPa; ③ Zirconia fiber reinforced zirconia aerogel thermal insulation composite material, with a heat resistance temperature of 1100°C and a density of 0.33-0.34 g / cm 3 The thermal conductivity at room temperature and 1100℃ are 0.021-0.024 W / (m·K) and 0.033-0.038 W / (m·K) respectively, the compressive strength is 3% deformation is 0.53-0.64 MPa, and the bending strength is 2.7-2.9 MPa.
Citation Information
Patent Citations
High strength carbon fiber reinforced silicon carbide ceramic matrix composite material and preparation method thereof
CN104844241A
An improved process for producing silica aerogel thermal insulation product with increased efficiency
CN107849764A
